2022
DOI: 10.1002/ddr.21975
|View full text |Cite
|
Sign up to set email alerts
|

Kukoamine A inhibits C‐C motif chemokine receptor 5 to attenuate lipopolysaccharide‐induced lung injury

Abstract: The aim of this study was to elucidate the mechanism underlying the effects of Kukoamine A (KuA) treatment on endotoxin-induced lung injury/inflammation. The study was performed in lipopolysaccharide (LPS)-exposed mouse models of lung injury and LPS-induced alveolar epithelial cell model. Relevant kits were used to detect levels of inflammation-related indicators, oxidative stress indicators, and mitochondrial function. Hematoxylin and eosin staining was to detect lung injury. Then, C-C motif chemokine recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, when added one hour before LPS, the three phenolamides were able to set differentiated THP-1 cells in an anti-inflammatory state that afterwards render them less sensible to the LPS pro-inflammatory stimulus. The ability of Kuk_A to counteract LPS-induced proinflammation was very recently described by Liu et al and Wang et al in other cells than macrophages [ 46 , 47 ]. Liu et al used an in vivo mouse model of lung injury with LPS, and an in vitro model of alveolar epithelial cells preincubated with LPS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, when added one hour before LPS, the three phenolamides were able to set differentiated THP-1 cells in an anti-inflammatory state that afterwards render them less sensible to the LPS pro-inflammatory stimulus. The ability of Kuk_A to counteract LPS-induced proinflammation was very recently described by Liu et al and Wang et al in other cells than macrophages [ 46 , 47 ]. Liu et al used an in vivo mouse model of lung injury with LPS, and an in vitro model of alveolar epithelial cells preincubated with LPS.…”
Section: Discussionmentioning
confidence: 98%
“…Liu et al used an in vivo mouse model of lung injury with LPS, and an in vitro model of alveolar epithelial cells preincubated with LPS. In both models, they demonstrated that Kuk_A decreased the expression of inflammatory factors and oxidative stress markers that were dependent of CCR5 inhibition [ 46 ]. In the same manner, Wang et al demonstrated that Kuk_A added in cell culture medium of nucleus pulposus cells preincubated with LPS, attenuated LPS-induced apoptosis, extracellular matrix degradation, and inflammation.…”
Section: Discussionmentioning
confidence: 99%